E-COMMERCE LOGISTICS EFFICIENCY, DELIVERY COSTS, AND ONLINE PURCHASE FREQUENCY IN SOUTH AFRICA - AGBEYINKA YINKA IBRAHIM (International Studies Journal)
Rising delivery costs and inconsistent logistics performance pose significant challenges to sustaining consumer engagement in South Africa’s digital commerce environment. This study investigated the influence of e-commerce logistics efficiency and average delivery cost per order on online purchase frequency. Anchored in the Technology Acceptance Model and Last-Mile Delivery Theory, the study employed a quantitative, explanatory design using secondary data from reputable sources, including Statista, UNCTAD, and the South African E-commerce Insights Report. The target population comprised South African online shoppers, with a sample drawn through purposive selection of datasets covering 36 monthly observations between 2020 and 2024. Multiple linear regression analysis was used to assess the direct effects of the independent variables on the dependent variable. Findings revealed that higher logistics efficiency significantly increased purchase frequency, while elevated delivery costs harmed repeat buying behavior. The study concluded that enhancing delivery operations and offering cost-sensitive shipping strategies are essential to deepening consumer loyalty. It recommends the adoption of tracking technologies and loyalty-based delivery discounts.